2023
DOI: 10.20517/cdr.2022.108
|View full text |Cite
|
Sign up to set email alerts
|

Targeting regulated cell death pathways in acute myeloid leukemia

Abstract: The use of the BCL2 inhibitor venetoclax has transformed the management of patients with acute myeloid leukemia (AML) who are ineligible for intensive chemotherapy. By triggering intrinsic apoptosis, the drug is an excellent illustration of how our greater understanding of molecular cell death pathways can be translated into the clinic. Nevertheless, most venetoclax-treated patients will relapse, suggesting the need to target additional regulated cell death pathways. To highlight advances in this strategy, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 168 publications
(277 reference statements)
0
8
0
Order By: Relevance
“…The introduction of venetoclax, a BCL2 inhibitor, has signi cantly changed the treatment approach for acute myeloid leukemia (AML) patients unable to undergo aggressive chemotherapy. This drug has effectively triggered intrinsic apoptosis, demonstrating the practical application of our understanding of molecular cell death processes in the medical eld [9].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The introduction of venetoclax, a BCL2 inhibitor, has signi cantly changed the treatment approach for acute myeloid leukemia (AML) patients unable to undergo aggressive chemotherapy. This drug has effectively triggered intrinsic apoptosis, demonstrating the practical application of our understanding of molecular cell death processes in the medical eld [9].…”
Section: Introductionmentioning
confidence: 95%
“…In general, the intricate interplay and communication among programmed cell death pathways highlight the complexity of cellular regulation, offering opportunities to understand disease mechanisms and develop innovative therapeutic interventions. Developing new drugs to treat AML patients who are resistant to intrinsic apoptosis is a promising approach that can be achieved by gaining a deeper understanding of the molecular pathways that regulate cell death [9].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, MOMP is blocked by a series of proteins that have an anti-apoptotic action, including BCL2, BCL-XL, and MCL1. When the balance between pro- and anti-apoptotic signals turns toward cell death due to internal or external stressors, the BAX and BAK proteins are activated and form pores in the mitochondrial outer membrane, subsequently releasing cytochrome c and inducing caspase activation [ 12 ].…”
Section: Rationale Of Bcl2 Inhibitionmentioning
confidence: 99%
“…Therefore, a better understanding of VEN resistance is crucial to developing new therapeutic strategies and improving the survival of VEN-AZA R/R AML [ 6 ]. Recent reviews have pinpointed the role of genetic and non-genetic factors in the apparition of resistance [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In this review, we will describe the main mechanisms of resistance and the therapeutic strategies to overcome them.…”
Section: Introductionmentioning
confidence: 99%
“…The Bcl2-inhibitor venetoclax is used in the treatment of various malignancies, including AML, and various lymphoid malignancies [103][104][105][106][107][108][109]. A recent study identified CK2 as a major regulator of resistance to venetoclax in mantle cell lymphoma; additional experimental studies have demonstrated that even though the CK2 inhibitor CX-4945/silmitasertib alone does not affect the viability of mantle cell lymphoma cell lines or primary samples, CK2 inhibition strongly synergizes with the antilymphoma effects of venetoclax and the Bruton's tyrosine kinase inhibitor ibrutinib [106][107][108].…”
Section: Combination Of Pk2 Inhibition and The Bcl2 Inhibitor Venetoc...mentioning
confidence: 99%